2019
DOI: 10.1007/s11695-018-03661-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying Enhanced Recovery After Bariatric Surgery (ERABS) Protocol for Morbidly Obese Patients With End-Stage Renal Failure

Abstract: Background In 2015 our hospital implemented the ERABS protocol. From that moment also morbidly obese patients with endstage renal disease (ESRD) were enrolled. The objective of this study was to evaluate the potential benefits and safety of the ERABS protocol for ESRD morbidly obese patients compared with patients who are morbidly obese patients undergoing bariatric surgery. Methods A retrospective review of a prospectively collected database was conducted for ESRD patients who underwent bariatric surgery acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, often due to obesityassociated comorbidities, their access to the transplant list and transplantation is inferior to non-obese [5,33]. Bariatric surgery is considered as a safe method of obesity treatment in that specific group of patients and feasible as a bridge therapy to kidney transplantation [6,[34][35][36]. Additionally, weight loss after bariatric surgery may improve kidney function to an acceptable level and delay the qualification to dialysis therapy in patients undergoing bariatric surgery before ESKD development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, often due to obesityassociated comorbidities, their access to the transplant list and transplantation is inferior to non-obese [5,33]. Bariatric surgery is considered as a safe method of obesity treatment in that specific group of patients and feasible as a bridge therapy to kidney transplantation [6,[34][35][36]. Additionally, weight loss after bariatric surgery may improve kidney function to an acceptable level and delay the qualification to dialysis therapy in patients undergoing bariatric surgery before ESKD development.…”
Section: Discussionmentioning
confidence: 99%
“…It was proven that obesity limits, or at least delays, access to kidney transplantation [5]. Bariatric surgery is considered a safe method to achieve rapid and sustainable weight loss before kidney transplantation [6]. Pretransplant weight loss may allow to sustain body weight and prevent common posttransplant weight gain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Study search and selection for very-low-energy diet (VLED) studies were higher in another three. 30,35,37 Of these, there was no increased complication risk in studies in which patients were matched for baseline co-morbidities, 21,40 but an increased risk in studies where the ESKD population had higher baseline co-morbidities, 30,35,37 with pulmonary complications, 30,37 infections 37 and cardiac arrest 30 more commonly reported, although overall events were low. Laparoscopic Roux-en-Y gastric bypass was associated with a higher complication rate than SG or AGB in one retrospective electronic database analysis.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Outcomes following sleeve gastrectomy (SG) were reported in 20 studies, 20,21,23,24,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] gastric bypass (GB) in 17 studies, [19][20][21][22][23][24][25][27][28][29][30]33,[35][36][37]41,42 adjustable gastric banding (AGB) in 10 studies, [20][21][22][23][27][28][29][30]33,41 and duodenal switch in two studies. 22,41 Fifteen studies reported on multiple bariatric surgery techniques.…”
Section: Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation